EPISTEMOLOGY IN THE CONTEXT OF THE MODERN BIOLOGICAL EVOLUTIONAL PARADIGM - О. S. Tokovenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the work is finding the reasonability of using bio-evolutionary paradigm for researching ratio morphic cognitive activity. Methodology. Methodological grounds consist of the original principles and conceptual apparatus of evolutionary epistemology. Scientific novelty. The article identifies opportunities for using of biological and evolutionary paradigm to study the peculiarities of ratiomorphic cognitive backgrounds and their influence on the formation and development of human knowledge. Conclusions. The article concludes that together with the idea of hyper cycles (feedback loop with mutual transmission of information in cognitive process) the concept of ratiomorphic cognitive backgrounds, as well as attempts to examine cognitive processes based on the scientific criteria (empirical verification, explanatory power and ability to predict) should be certainly considered as a positive contribution to the development of evolutionary epistemology into modern epistemological research. However, it is also indicated the fact of narrowing the heuristic possibilities of this epistemological direction because of excessive metaphor of bio-evolutionary paradigm. Further development of evolutionary epistemological research is considered in shifting the emphasis from biological and evolutionary towards cultural and evolutionary paradigm.